Poroelastic Modeling of Highly Hydrated Collagen Hydrogels: Experimental Results vs. Numerical Simulation With Custom and Commercial Finite Element Solvers - Castro, André P. G.; Yao, Jiang; Battisti, Tom; Lacroix, Damien (Frontiers in Bioengineering and Biotechnology, 2018)
This study presents a comparison between the performances of two Finite Element (FE) solvers for the modelling of the poroelastic behaviour of highly hydrated collagen hydrogels. Characterization of collagen hydrogels has been a widespread challenge since this is one of the most used natural biomaterials for Tissue Engineering (TE) applications. V-Biomech® is a free custom FE solver oriented to soft tissue modelling, while Abaqus® is a general-purpose commercial FE package which is widely used for biomechanics computational modelling. Poroelastic simulations with both solvers were compared to two experimental protocols performed by Busby et al. (2013) and Chandran and Barocas (2004), also using different implementations of the frequently used Neo-Hookean hyperelastic model. The average differences between solvers outputs were under 5% throughout the different tests and hydrogel properties. Thus, differences were small enough to be considered negligible and within the variability found experimentally from one sample to another. This work demonstrates that constitutive modelling of soft tissues such as collagen hydrogels can be achieved with either V-Biomech or Abaqus standard options (without user-subroutine), which is important for the biomechanics and biomaterials research community. V-Biomech has shown its potential for the validation of biomechanical characterization of soft tissues, while Abaqus’ versatility is useful for the modelling and analysis of TE applications where other complex phenomena may also need to be captured.